Ethanol production and its environmental impacts in the alcoholic industry of Alagoas, Brazil - Novais, Roney Calheiros de; Magalhães, Ivomberg Dourado; Lima, Cícero Luiz Calazans de; Medeiros, Aldair de Sousa; Gonzaga, Giordano Bruno Medeiros (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Despite all the tradition of the sugarcane agro-industry, the concern and critical judgment related to the negative environmental impacts that its industrial processes can produce in the environment is notorious. The objective of this study was to evaluate the production of ethanol, sugar and other sugarcane by-products from four industrial units in Alagoas during three harvests and to assess the possible environmental impacts caused by the industrialization process. A survey was carried out with a questionnaire in three adjoining distilleries and an autonomous distillery, located in the state of Alagoas. The four distilleries led the batch fermentation fed (discontinuous fed process) and they have a fermenters lung. Two of them have opened fermenters and two closed fermenters, for the recovery of the ethanol dragged by the gases released during the ethanolic fermentation. The questionnaire was filled with operational data from each distillery. The raw material was evaluated by means of the variables sugarcane ground for sugar, cane ground for alcohol, ground cane, hourly grinding, type of must (broth / mixed / molasses), wort total reducing sugars. Production, residues, efficiencies and yields of the mills were quantified. The distilleries evaluated in this work use their residues within an acceptable range from the environmental point of view, always seeking better technologies in order to minimize environmental impacts. The industrial operating procedure adopted by the four units is, except for small variations, standard for the entire state of Alagoas.